The IgH Eµ-MAR regions promote UNG-dependent error-prone repair to optimize somatic hypermutation - Ophélie A. Martin; Morgane Thomas; Marie Marquet; Charlotte Bruzeau; Armand Garot; Mylène Brousse; Sébastien Bender; Sébastien Bender; Claire Carrion; Jee Eun Choi; Bao Q. Vuong; Patricia J. Gearhart; et al. (Frontiers in Immunology, 2023)
IntoductionTwo scaffold/matrix attachment regions (5’- and 3’-MARsEµ) flank the intronic core enhancer (cEµ) within the immunoglobulin heavy chain locus (IgH). Besides their conservation in mice and humans, the physiological role of MARsEµ is still unclear and their involvement in somatic hypermutation (SHM) has never been deeply evaluated.MethodsOur study analyzed SHM and its transcriptional control in a mouse model devoid of MARsEµ, further combined to relevant models deficient for base excision repair and mismatch repair.ResultsWe observed an inverted substitution pattern in of MARsEµ-deficient animals: SHM being decreased upstream from cEµ and increased downstream of it. Strikingly, the SHM defect induced by MARsEµ-deletion was accompanied by an increase of sense transcription of the IgH V region, excluding a direct transcription-coupled effect. Interestingly, by breeding to DNA repair-deficient backgrounds, we showed that the SHM defect, observed upstream from cEµ in this model, was not due to a decrease in AID deamination but rather the consequence of a defect in base excision repair-associated unfaithful repair process.DiscussionOur study pointed out an unexpected “fence” function of MARsEµ regions in limiting the error-prone repair machinery to the variable region of Ig gene loci.